A novel Fe3O4/graphene oxide/citrus peel-derived bio-char based nanocomposite with enhanced adsorption affinity and sensitivity of ciprofloxacin and sparfloxacin. (November 2019) - Zhou, Yue; Cao, Shurui; Xi, Cunxian; Li, Xianliang; Zhang, Lei; Wang, Guomin; Chen, Zhiqiong
Graphical abstract: Schematic diagram of the potential adsorption sites of bio-nanocomposites for removing CIP/SPA molecules and their proposed interaction mechanisms. Highlights: A series of engineered biochar were prepared by one-pot pyrolysis. The morphology and structural of biochars could be regulated with graphene oxide. The mGOCP showed high adsorption capacity for ciprofloxacin and sparfloxacin. Possible adsorption mechanisms were explained by Raman, kinetics and isotherms. The mGOCP has easy magnetic separation and recyclability for multiple reuses. Abstract: To create more active adsorption sites on biochar, the Fe3 O4 /GO/citrus peel-derived magnetic bio-nanocomposite (mGOCP) with hierarchically porous architectures was synthesized by a facile one-pot hydrothermal approach for efficient removal of fluoroquinolone antibiotics ciprofloxacin (CIP) and sparfloxacin (SPA). The characterization analysis of bio-nanocomposites showed that the incorporation of GO could ensure relatively higher surface area (1556 cm 2 g −1 ), more abundant pore structure, and higher thermal stability within mGOCP bio-nanocomposites than Fe3 O4 /citrus peel-derived magnetic bio-nanocomposites (mCP). And the mGOCP-1% attained outstanding adsorption capacity for CIP (283.44 mg g −1 ) and SPA (502.37 mg g −1 ), respectively. The primary adsorption mechanisms for CIP and SPA included π-π electron donor-acceptor interaction, H-bonding, hydrophobic interaction and electrostatic interaction. Overall, the surface morphology and structural composition of biochars could be regulated with GO to facilitate the adsorption capacity. Moreover, the developed mGOCP could be extended as a potential adsorbent for removal of other emerging organic pollutants in water.